Characteristics of a novel fluidic oscillator with movable feedback channels and resonators - Yan, Zhoujun; Lu, Yongtong; Yang, Xiangfen; Deng, Qiulin; Lu, Weiyu (Frontiers in Energy Research, 2023)
In this study, a novel fluidic oscillator suitable for use as a key component of a flow control device is proposed and investigated through numerical simulations. The new layout adds resonators to a typical fluidic oscillator with dual feedback channels, and the length of the feedback loop is designed to be adjustable. This fluidic oscillator with movable feedback channels and resonators can generate a jet with an adjustable frequency, and it has smaller total pressure loss than the baseline model. Numerical results show that the movement of the feedback channels regulates the degree of coupling between the feedback channels and resonators to generate different orders of jet frequencies. This self-excited fluidic oscillator with adjustable jet frequency is more adaptive than typical designs when dealing with complex flow separation conditions, and it will be more stable because the frequency adjustment requires neither high-frequency movable mechanisms nor external energy input. Moreover, the frequency switching phenomenon is observed in special cases, which may help improve the efficiency of the compressor blades with a drastically changed dominant frequency under off-design conditions or with multiple dominant frequencies, such as tip leakage flow and shock–boundary layer interaction.